2016
DOI: 10.1002/elps.201600399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of purified fractions from cell culture supernate of high‐density pre‐B acute lymphoblastic leukemia cells (ALL3) on the growth of ALL3 cells at low density

Abstract: The mechanisms underlying the aberrant growth and interactions between cells are not understood very well. The pre-B acute lymphoblastic leukemia cells directly obtained from an adult patient grow very poorly or don't grow at all at low density (LD), but grow better at high starting cell density (HD). We found that the LD ALL3 cells can be stimulated to grow in the presence of diffusible, soluble factors secreted by ALL3 cells themselves growing at high starting cell density. We then developed a biochemical pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 78 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…A newly established cell line freshly obtained from the leukemic cells growing as ascitic cells in the pleural effusion of a terminally ill patient with Ph+ acute lymphoblastic leukemia (ALL3) is used in this work. ALL3 is a clonal proliferation of p190 BCR-ABL transformed pre B cells that arise in the bone marrow [30,34]. We observed that there is a significant difference in the growth rate of ALL3 cells at low (LD) and high starting cell densities (HD).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A newly established cell line freshly obtained from the leukemic cells growing as ascitic cells in the pleural effusion of a terminally ill patient with Ph+ acute lymphoblastic leukemia (ALL3) is used in this work. ALL3 is a clonal proliferation of p190 BCR-ABL transformed pre B cells that arise in the bone marrow [30,34]. We observed that there is a significant difference in the growth rate of ALL3 cells at low (LD) and high starting cell densities (HD).…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of cell-cell communication on biomechanical properties of cells has not been systematically studied. At the same time, it is known that the collective behavior is an important feature and it is involved in regulating many biological processes such as cell migration, stem cell maintenance, growth of proper organ size, immune system regulation, hematopoiesis, homeostasis and regeneration [27][28][29][30][31][32][33][34]. Individual cells utilize 'autocrine' and/or 'paracrine' factors to coordinate these beneficial collective behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations